The effect of competence and organization culture to employee performance with motivation as the mediation variable in the Directorate General of Fiscal balance-Ministry of Finance, Indonesia - Acep Dedi Supriadi; Suharto Suharto; Sodikin Sodikin (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
High employee performance can be achieved if all elements within the organization can be well integrated. Increased employee competence, application of organizational culture and employee motivation are part of the elements or variables that affect an employee performance. This research aims to determine and analyze the influence of competence and organizational culture on employee performance through motivation as a variable mediation. The population in this research is all Civil Servant of Directorat General of Fiscal Balance (DGFB) which amounted to 426 people. Sampling method is Simple Ramdom Sampling (SRS) with the number of respondents as much as 80 employees calculated based on Slovin Formula. Data collection techniques in this study are literature study and questionnaire. Data were analyzed by path analysis model by using SPSS. The first results of this researh showed that the competence and organizational culture simultaneously had a positive and significant effect on motivation. Furthermore, based on the results of partial tests, competence have a positive but not significant effect on motivation, while the influence of organizational culture on motivation is positive and significant.The second result shows that the competence, organizational culture, and motivation have positive and significant effect on employee performance. Furthermore, based on the results of partial tests, competence and organizational culture show the same results that have a positive and significant effect on employee performance, while motivation effects on employee performance although still positive but not significant.